The Trans-Pacific Partnership investment chapter sets a new worldwide standard - Mélida Hodgson (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
Seen in the context of the United States' international investment agreement practice, the Trans-Pacific Partnership includes several new features – expanding regulatory space for states on environment, health and finance but also backtracking on an appellate mechanism. The author highlights developments that could have systemic impacts on investment agreements worldwide.
Keywords: 330